1996
DOI: 10.1029/96jc01064
|View full text |Cite
|
Sign up to set email alerts
|

Winter upwelling off Luzon in the northeastern South China Sea

Abstract: A major upwelling region centered about 100 km offshore between 16° and 19°N off northwest Luzon in the South China Sea is revealed in the distributions of temperature, salinity, and dissolved oxygen concentration during a cruise in December 1990. Upward movement of water low in dissolved oxygen can be identified to a depth of 300 m. Climatological distributions of temperature and upper ocean heat content and tracer distribution obtained from a recent numerical experiment lend support to the existence of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 15 publications
(7 reference statements)
11
94
0
1
Order By: Relevance
“…2. They are consistent with the general features reported previously for South China Sea waters (Gong et al 1992;Chen and Huang 1996;Shaw et al 1996;Lin et al 1999;Chen et al 2001;Wong et al 2002), and have been used frequently to distinguish them from other water masses (e.g., the Western Philippine Sea water) upon mixing. As shown in …”
Section: The Seasonal Hydrography At the Seats Sitesupporting
confidence: 79%
“…2. They are consistent with the general features reported previously for South China Sea waters (Gong et al 1992;Chen and Huang 1996;Shaw et al 1996;Lin et al 1999;Chen et al 2001;Wong et al 2002), and have been used frequently to distinguish them from other water masses (e.g., the Western Philippine Sea water) upon mixing. As shown in …”
Section: The Seasonal Hydrography At the Seats Sitesupporting
confidence: 79%
“…Obviously, the study area is away from the previously reported coastal upwelling regions in the SCS (Shaw et al, 1996;Jing et al, 2009;Gan et al, 2009) but partly includes the South East Asia Time-Series Station (SEATS station, Wong et al, 2007). The bottom topography is relatively uniform with domain averaged depth >3500 m.…”
Section: Study Areamentioning
confidence: 99%
“…Tang et al (1999) and Wang et al (2010) investigated the winter phytoplankton bloom phenomena occurred off the southwest of Luzon Strait in winter using both satellite derived data and shipboard measurements. They suggested that the phytoplankton bloom was mainly attributed to the winter upwelling occurring there (Shaw and Chao, 1994;Shaw et al, 1996). Using a three dimensional coupled physical-biogeochemical model, Liu et al (2002Liu et al ( , 2007 examined the spatial and temporal distributions of chlorophyll-a and primary production under the influence of monsoon winds in the SCS.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the upwelling is difficult to detect from satellite-derived sea surface temperature (SST) images (Udarbe-Walker and Villanoy, 2001). Shaw et al (1996) initially reported this winter upwelling, pointing out that the upwelling in this area was affected by a remotely forced component arising from the basin-wide gyre circulation. However, Shaw's results were based on only one cruise in December, 1990.…”
Section: Introductionmentioning
confidence: 99%